A high-gain cladded waveguide amplifier on erbium doped thin-film lithium niobate fabricated using photolithography assisted chemo-mechanical etching - Liang, Youting; Zhou, Junxia; Liu, Zhaoxiang; Zhang, Haisu; Fang, Zhiwei; Zhou, Yuan; Yin, Difeng; Lin, Jintian; Yu, Jianping; Wu, Rongbo; Wang, Min; Cheng, Ya (Nanophotonics (Berlin, Germany), 2022)
Erbium doped integrated waveguide amplifier and laser prevail in power consumption, footprint, stability and scalability over the counterparts in bulk materials, underpinning the lightwave communication and large-scale sensing. Subject to the highly confined mode in the micro-to-nanoscale and moderate propagation loss, gain and power scaling in such integrated devices prove to be more challenging compared to their bulk counterparts. In this work, a thin cladding layer of tantalum pentoxide (Ta ) is employed in the erbium doped lithium niobate (LN) waveguide amplifier fabricated on the thin film lithium niobate on insulator (LNOI) wafer by the photolithography assisted chemo-mechanical etching (PLACE) technique. Above 20 dB small signal internal net gain is achieved at the signal wavelength around 1532 nm in the 10 cm long LNOI amplifier pumped by the diode laser at ∼980 nm. Experimental characterizations reveal the advantage of Ta cladding in higher optical gain compared with the air-clad amplifier, which is further explained by the theoretical modeling of the LNOI amplifier including the guided mode structures and the steady-state response of erbium ions.